The Experience of Being a Manager - Cole, Rosanna (2006)
Mid hierarchical managers have a number of different pressures placed on them at work, as they are responsible for the output of junior staff, they must liaise with peers at the same organisational level and report to superiors on a regular basis. Thus, there are a number of interactions that they are involved with. In the social sciences, a relatively new approach is that they manage these interactions to create impressions that fit with the context of the situation, referred to as identity work. Additionally, the manager's behaviour at work may be influenced by home life pressures which would also be unique to the individual. Hence, the manager is faced with a double control problem of managing his or her own life whilst managing a team at work, which can be riddled with a variety of complex social relationships. Using case study analysis of individual managers, this research investigates the main challenges, rewards and difficulties of being a middle manager in a large modern corporation and detects the strategic implications of these experiences and circumstances of the manager.